Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Kedai Kopi Kulo Di Samarinda - Armini Ningsih; Andi Nurhasanah; Syachrul Syachrul; Putri Afriliyani (Politeknik Negeri Samarinda, 2021)
Service quality is an important aspect for the development of the company. Currently, most consumers are starting to make quality as the main parameter in making choices about a product/service. Moreover, quality is often used as a mean of promotion that is automatically able to increase/decrease the selling value of the company's products. This study aims to determine how much service quality influence on customer satisfaction at the Kulo Coffee Shop in Samarinda. This study uses quantitative methods. The data of this study were obtained from questionnaires distributed online using the Incidental Sampling technique. The population of this study were people who had bought or consumed Kulo coffee products, the sample used was 104 respondents. This research was conducted with validity test, reliability test, simple linear regression analysis test, coefficient of determination test and t test (partial) which was processed with the help of SPSS 25 Statistic for windows software. The results of the study found that the hypothesis in this study has been significantly proven. Service quality has a significant effect on customer satisfaction, the correlation coefficient is 0.862 and the coefficient of determination is 0.742. The implication of this research is that service quality has equally important role either individually or simultaneously in increasing customer satisfaction at the Kulo Coffee Shop in Samarinda.